2016
DOI: 10.1042/bst20160221
|View full text |Cite
|
Sign up to set email alerts
|

Motility and adhesion through type IV pili in Gram-positive bacteria

Abstract: Type IV pili are hair-like bacterial surface appendages that play a role in diverse processes such as cellular adhesion, colonization, twitching motility, biofilm formation, and horizontal gene transfer. These extracellular fibers are composed exclusively or primarily of many copies of one or more pilin proteins, tightly packed in a helix so that the highly hydrophobic amino-terminus of the pilin is buried in the pilus core. Type IV pili have been characterized extensively in Gram-negative bacteria, and recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 57 publications
0
52
0
Order By: Relevance
“…Symbiosis requires machinery for cell‐to‐cell contact between the interacting partners. The T4P constitutes a system for cell adhesion, biofilm formation, motility, secretion and DNA uptake (Bahar, Goffer, & Burdman, ; Piepenbrink & Sundberg, ). It was shown that T4P assists host colonization by a gut symbiont (Powell, Leonard, Kwong, Engel, & Moran, ).…”
Section: Discussionmentioning
confidence: 99%
“…Symbiosis requires machinery for cell‐to‐cell contact between the interacting partners. The T4P constitutes a system for cell adhesion, biofilm formation, motility, secretion and DNA uptake (Bahar, Goffer, & Burdman, ; Piepenbrink & Sundberg, ). It was shown that T4P assists host colonization by a gut symbiont (Powell, Leonard, Kwong, Engel, & Moran, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, most bacteria exist in close association with substrates and developed a variety of tools to mediate motion over a wide range of surfaces such as hulls of ships [3], medical catheters [4] and within the human body [5,6]. Many bacteria, both gram-negative (such as Neisseria meningitidis [7], Pseudomonas aeruginosa [8][9][10] and Myxococcus xanthus [11]) and grampositive (such as Clostridium difficile [12,13]), use socalled type IV pili for the motion over substrates and attachment to other cells. Pili are several microns long filaments that emerge from the surface of cells.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the knowledge on the biology of Tfp was generated from studies on Gram-negative pathogens (10), in which Tfp are often critical for their pathogenic capacity. Recent advances in genomic sequencing have led to the discovery that the pil cluster is also present in Gram-positive bacteria (11,12). Tfp in Gram-positive bacteria exhibit biological functions similar to those seen in Gram-negative bacteria, including adherence to both biotic and abiotic surfaces, surface-dependent twitching motility, and DNA uptake in naturally competent bacteria.…”
mentioning
confidence: 99%